IMPROVING MULTIPLICATION SKILLS THROUGH NUMBER CARDS BASED ON DIFFERENTIATED CONTENT FOR CHILDREN WITH LEARNING DIFFICULTIES - Luther Duma; Cepi Safiruddin; Lis Prasetyo; Fery Muhammad Firdaus; Rendy Roos Handoyo (Jurnal Kajian Pendidikan dan Psikologi, 2026)
Multiplication skills are one of the fundamental mathematical abilities that play an important role in supporting the mastery of advanced mathematical concepts. However, slow learners often experience difficulties in understanding multiplication concepts due to limitations in processing abstract information, memorizing numerical facts, and requiring longer learning time compared to their peers. This study aimed to improve multiplication computation skills through the implementation of number card media based on content-differentiated instruction for slow learners in Grade VII at SMP Negeri 2 Muara Ancalong. The study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, which was conducted in two cycles consisting of planning, action implementation, observation, and reflection stages. The research participants were slow learners in Grade VII who experienced difficulties in understanding and solving multiplication problems. Data were collected through observation, mathematical ability tests, documentation, and field notes, and were analyzed using quantitative and qualitative descriptive approaches. The results showed a gradual improvement in students’ multiplication computation skills from the pre-cycle stage to Cycle II. The use of number card media assisted students in understanding multiplication concepts through visual representations and manipulative learning activities, while content differentiation enabled teachers to adjust learning materials according to students’ ability levels and individual learning needs. The findings indicate that the integration of concrete media and differentiated content instruction effectively improved calculation accuracy, conceptual understanding, and mathematics learning independence among slow learners. This study provides practical implications for developing more adaptive, concrete, and student-centered inclusive mathematics instruction that accommodates individual learning characteristics.